A critique of the Washington Consensus - Malan, Pedro S. (1991)
This was the intervention of the author at the closing Panel of a Conference inHonor of Albert Hirschman on Development Strategies for Latin America. It draws attentionto some shortcomings of the so-called “Washington Consensus”, John Williamson’s aptexpression to describe the view that better policies lead to better results, worse policies toworse results. This is true but trite, trivial and tautological. The author suggests that thereare three types of policies to be addressed: the first is related to the quest for macroeconomicstability; the second to much-needed microeconomic reforms; the third is the missing linkin the Washington Consensus and has to do with the resumption of growth and investmentwith technological change in an increasingly competitive world economy. This requires, inaddition to macro- stability and micro-reforms, some visions of the future and a much moreeffective pattern of interactions between the private sector and a modernized and activepublic sector, given the interdependence of investment decisions in the presence of economywideexternalities. JEL Classification: B22; O11; O43.